Explanations about Poverty Origin According to Professional Training Area - Bastias, Franco (2019)
The way in which individuals and groups explain poverty shapes how they relate to it. This paper inquires the beliefs of university students about the causes of poverty and analyses the relation of these beliefs with their professional training area. An assessment instrument that considers three type of attributions -individualist, socio-structural and fatalistic-, was administered to a sample of 448 advanced university students belonging to nine social sciences programs, aged between 19 and 42 years (M = 22.92; SD = 3.12). The results obtained indicate important variations in the explanations about poverty according to the professional training area. Students of economic sciences emphasized the importance of individual factors, psychology and law students tended to mixed explanations and sociology students showed a wide preference for socio-structural causes over individual and fatalistic causes. The implications of attributional process in the behavior of these future professionals towards economically disadvantaged populations are discussed.